Post-Covid-19 Pandemic, Innovation of Local Government Policy Perspective of State Administration Law - Arzhi Jiwantara, Firzhal; Nasaruddin, Nasaruddin (Devotion : Journal of Research and Community Service, 2022)
Handling Post-Covid-19 Pandemic within the framework of a unitary state is not only the responsibility of the central government but also the roles and responsibilities of local governments. This is important for the government to innovate policies for handling the post-Covid-19 pandemic without overriding the policies that have been issued by the central government. This study aims to identify innovations in local government policies in handling the Post-Covid-19 pandemic from the perspective of Administrative Law. The research was conducted in a normative juridical manner with a qualitative approach to the urgency of local government policy innovation in handling the Post-Covid-19 pandemic. In this case, an analysis of Mataram City's regional policies is needed in handling the Post-Covid-19 Pandemic. This gives an understanding that local governments in making policies need synchronization with the central government, especially in analyzing a policy in accordance with state administrative law. The forms of policy innovations carried out by local governments in handling the post-Covid-19 pandemic include: 1) Strengthening the Regional Health System; 2) Strengthening the Social Protection System; and 3) Economic Recovery